2019
DOI: 10.1002/brb3.1410
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence between dorsal and ventral hippocampus during spatial navigation

Abstract: Introduction The hippocampus is linked to the formation and retrieval of episodic memories and spatial navigation. In rats, it is an elongated structure divided into dorsal (septal) and ventral (temporal) regions paralleling the respective division in the posterior and anterior hippocampus in humans. The dorsal hippocampus has been suggested to be more important for spatial processing and the ventral to processing anxiety‐based behaviors. Far less is known regarding the degree to which these different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 79 publications
3
14
0
Order By: Relevance
“…It was found that spatial performance was also significantly impaired when silencing the whole hippocampi, and similarly impaired in bilateral dHPC and the vHPC inactivations. Ipsilateral inactivations (in one hemisphere) showed only minor impairment, but inactivation of one dHPC and the contralateral vHPC resulted in remarkable deficits, resembling bilateral inactivations ( Lee et al, 2019 ). Overall, despite the initial opinion that the vHPC is not involved in spatial learning, newer studies have shown that the vHPC is indeed needed for spatial learning and the representation of spatial memories, and together with the above-mentioned findings, it can be concluded that the whole hippocampus, acting as a unitary structure, is needed for spatial processing.…”
Section: Introductionsupporting
(Expert classified)
See 1 more Smart Citation
“…It was found that spatial performance was also significantly impaired when silencing the whole hippocampi, and similarly impaired in bilateral dHPC and the vHPC inactivations. Ipsilateral inactivations (in one hemisphere) showed only minor impairment, but inactivation of one dHPC and the contralateral vHPC resulted in remarkable deficits, resembling bilateral inactivations ( Lee et al, 2019 ). Overall, despite the initial opinion that the vHPC is not involved in spatial learning, newer studies have shown that the vHPC is indeed needed for spatial learning and the representation of spatial memories, and together with the above-mentioned findings, it can be concluded that the whole hippocampus, acting as a unitary structure, is needed for spatial processing.…”
Section: Introductionsupporting
(Expert classified)
“…A more recent study investigated intercommunication between the dHPC and the vHPC during the MWM task learning in rats ( Lee et al, 2019 ). In this study, the activity of the hippocampi was locally inhibited by muscimol in bilateral or combined inactivations.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with present results, a recent study found that both the HPCd and HPCv were critical for food reward-directed spatial navigation in an obstacle-rich complex environment (47). Under certain testing conditions, spatial learning and memory in an aversive reinforcement-based water maze also requires both subregions of the HPC (48). Similarly, whole-brain analysis of blood flow in rats during retrieval of spatial memory in an aversive reinforcement-based Barnes maze task revealed increased activation in the CA1d and CA1-3v in trained animals compared with controls (49).…”
Section: Discussionsupporting
confidence: 91%
“…Although MUS-V rats often had some scores that were intermediary between PBS and MUS-D rats, their overall pattern closely resembled the PBS pattern in all respects. The absence of any effect in the MUS-V condition was somewhat unexpected, given the central position of the ventral intermediate hippocampus and the interdependence between dorsal and ventral hippocampus in information processing (Lee et al, 2019) as well as its connections with the medial prefrontal cortex, a structure important for behavioral flexibility (Ragozzino et al, 1999;Hoover and Vertes, 2007). Although it is possible that more extensive inactivations could yield significant alterations of VTE behavior, they would also likely result in performance deficits, thus making it difficult to disentangle specific effects on…”
Section: Discussionmentioning
confidence: 99%